Exploring the potential of kenaf seed proteins produced via freeze, spray and vacuum oven drying: A comparison with commercial soy and whey proteins - Arulrajah, Brisha; Qoms, Mohammed S.; Barkia, Ines; Wan Ibadullah, Wan Zunairah; Zakaria, Muta Harah; Saari, Nazamid (Elsevier B.V., 2025)
The effect of freeze drying (FD), spray drying (SD) and vacuum oven drying (VOD) on the structural, thermal, physicochemical and techno-functional properties of kenaf seed proteins was studied. Their functional performance was also compared with commercial soy protein (SP) and whey protein (WP). Microstructural observation revealed distinct morphologies, with FD exhibiting a plate-like structure, SD producing spherical particles and VOD resulting in a block structure. FD and SD exhibited similar molecular weight distributions, greater structural flexibility and lower surface hydrophobicity compared to VOD. All drying methods exhibited high and comparable thermal denaturation temperature. SD produced the lightest-coloured protein powder, closely resembling the colour of commercial SP and WP. The essential amino acids content of FD, SD and VOD was comparable to that of SP and WP. Based on functional performance, FD and SD showed the highest solubility, oil holding capacity (OHC) and foaming properties; FD exhibited excellent emulsion properties; VOD demonstrated superior water holding capacity (WHC); and SD exhibited the best gelling properties. Notably, FD, SD and VOD of kenaf seed protein outperformed commercial SP and WP in most functional properties, except for solubility and gelling (WP) and WHC (SP), highlighting their promising potential as sustainable plant-based protein alternative.